Primary and vicarious posttraumatic growth following genocide, war and humanitarian emergencies: an interpretative phenomenological analysis - McCormack, Lynne Maree (2010)
There is little research into the ‘lived’ experience of individuals exposed to war, genocide or humanitarian emergencies. Similarly, little is known about the positive and negative psychological processes following such complex psychosocial events for reconstructing lives. Using Interpretative Phenomenological Analysis (IPA), this thesis sought to offer subjective insights into the unique experiential world of aid personnel, military veterans and their wives from both a primary and vicarious perspective. IPA is a detailed examination of an individual’s lived experience of a particular event. It seeks the insider’s perspective through a process of iterative interpretative activity. Data from semi-structured interviews revealed both negative and positive interpretations. Negative aspects included trauma betrayal, shame, narcissistic self harm, rageful anger and moral doubt. The positive domains of empathy, love, humility and gratitude, aspects of posttraumatic growth that are not captured by existing standardised psychometric tools of growth, assisted meaning making for redefining lives over time. This thesis critiques: first, the predilection for positivist research paradigms rather than phenomenological understanding to inform psychological practice and research; second, the commodification of traumatic phenomena as emotional capital; and third, my personal experience using IPA. In summary, theories of growth to date posit social support as a necessary condition for growth following adversity. However, when social support is absent or even antagonistic I propose that a unique dispositional profile that incorporates a strong altruistic identity can stimulate meaning making and posttraumatic growth. A strong altruistic identity is committed to assisting those in need despite the risk of personal threat or cost. It also has the reciprocal benefit of developing personal and social wellbeing in the giver. For the participants of this thesis, the growthful domains of love, empathy, gratitude and humility, all aspects of an altruistic identity, appeared to generate renewed moral integrity and self reparation for psychological growth.